Influence of alveolar bone thickness and bucco-palatal inclination on root resorption of lateral incisors in unilateral maxillary impacted canines: a retrospective observational study - Weiman Sun; Yuanyuan Yang; Chenghuan Liu; Houxuan Li; Lang Lei (BMC Oral Health, 2024)
Abstract Background This study aimed to investigate the potential associations between alveolar bone thickness, bucco-palatal inclination of maxillary lateral incisors, and lateral incisor root resorption in patients with unilateral maxillary impacted canines (UMICs). Methods A total of three hundred and five subjects (120 males, 185 females; mean age, 16.39 years; standard deviation, 4.04) with UMICs were included. Canine position and root resorption were assessed using CBCT. UMICs were divided into palatal, buccal and mid-alveolus groups (PICs, BICs and MAICs), with 117, 137 and 51 subjects, respectively. Alveolar bone thickness and bucco-palatal inclination of lateral incisors were measured using the Dolphin software. Results The prevalence of lateral incisor root resorption was significantly lower in the BICs (13.9%) than MAICs (29.4%) and PICs (29.1%). Alveolar bone thickness of the apical area was smaller in UMICs with lateral incisor root resorption than no resorption in both PICs (8.33 ± 1.64 vs 10.53 ± 2.55 mm) and BICs (8.94 ± 1.85 vs 10.76 ± 2.28 mm). Furthermore, lateral incisors on the impacted side were more buccally inclined in PICs with lateral incisor root resorption than no resorption, while in both BICs and MAICs, there was no statistical difference between lateral incisor root resorption than no resorption. Moreover, alveolar bone thickness of the apical area, rather than bucco-palatal inclination of lateral incisors, was significantly correlated with lateral incisor root resorption both in PICs and BICs. Conclusions Lateral incisor root resorption is less common in BICs. Thinner alveolar bone thickness at the apical area of lateral incisors can be considered as a potential risk factor for lateral incisor root resorption in UMICs.